Vascular Endothelial Cell Function in Catastrophic Antiphospholipid Syndrome: A Case Report and Review of the Literature - B. Routy; T. Huynh; R. Fraser; C. Séguin (Case Reports in Hematology)
Catastrophic antiphospholipid syndrome (CAPS) is a rare autoimmune condition, which has been associated with a high mortality rate. However, with current management that includes a combination of anticoagulation, glucocorticoid administration, and plasma exchange, mortality rate has declined. Despite survival improvement with new generation immunosuppressive agents, their mechanisms of action are poorly defined, and CAPS is still considered a high-risk complication in patients known with antiphospholipid antibody syndrome. Herein, we present a case of a 79-year-old male who presented with a myocardial infarct and renal failure secondary to CAPS following a splenectomy for immune thrombocytopenia. Regardless of rapid combination of first-line treatment and rituximab therapy, the patient developed lethal cardiogenic shock secondary to mitral valve papillary muscle necrosis. Discussion of the pathophysiology and avenues of future therapies in CAPS are reported.